A problem by Siddharth Jayshankar

Level pending

If 0.9 3 0.7 3 = 0.0775 \sqrt [ 3 ]{ 0.9 } -\sqrt [ 3 ]{ 0.7 } = 0.0775 , then 2 0.81 3 + 0.63 3 + 0.49 3 \frac { 2 }{ \sqrt [ 3 ]{ 0.81 } +\sqrt [ 3 ]{ 0.63 } +\sqrt [ 3 ]{ 0.49 } } =?

1.163 2.325 0.775 0.388

This section requires Javascript.
You are seeing this because something didn't load right. We suggest you, (a) try refreshing the page, (b) enabling javascript if it is disabled on your browser and, finally, (c) loading the non-javascript version of this page . We're sorry about the hassle.

1 solution

0.9 3 0.7 3 = 0.0775 \sqrt [ 3 ]{ 0.9 } -\sqrt [ 3 ]{ 0.7 } =0.0775\\

Using ( a b ) 3 = a 3 b 3 3 a b ( a b ) { (a-b) }^{ 3 }={ a }^{ 3 }-{ b }^{ 3 }-3ab(a-b)

( 0.9 3 0.7 3 ) 3 = 0.9 0.7 3 0.9 × 0.7 3 ( 0.9 3 0.7 3 ) { (\sqrt [ 3 ]{ 0.9 } -\sqrt [ 3 ]{ 0.7 } ) }^{ 3 }=0.9-0.7-3\sqrt [ 3 ]{ 0.9\times 0.7 } (\sqrt [ 3 ]{ 0.9 } -\sqrt [ 3 ]{ 0.7 } )\\ ( 0.0775 ) 3 = 0.2 3 ( 0.63 3 ) ( 0.0775 ) { (0.0775) }^{ 3 }=0.2-3(\sqrt [ 3 ]{ 0.63 } )(0.0775)

3 ( 0.63 3 ) = 0.2 ( 0.0775 ) 3 ( 0.0775 ) = 0.2 ( 0.0775 ) ( 0.0775 ) 2 3(\sqrt [ 3 ]{ 0.63 } )=\frac { 0.2-{ (0.0775) }^{ 3 } }{ (0.0775) } =\frac { 0.2 }{ (0.0775) } -{ (0.0775) }^{ 2 }


0.81 3 + 0.49 3 + 0.63 3 = ( 0.9 3 ) 2 + ( 0.7 3 ) 2 + 0.9 × 0.7 3 \sqrt [ 3 ]{ 0.81 } +\sqrt [ 3 ]{ 0.49 } +\sqrt [ 3 ]{ 0.63 } ={ (\sqrt [ 3 ]{ 0.9 } ) }^{ 2 }+{ (\sqrt [ 3 ]{ 0.7 } ) }^{ 2 }+\sqrt [ 3 ]{ 0.9\times 0.7 }

A d d i n g a n d s u b t r a c t i n g 2 ( 0.9 × 0.7 ) 3 , Adding\quad and\quad subtracting\quad 2(\sqrt [ 3 ]{ 0.9\times 0.7 )} ,

{ 0.9 3 ) 2 + ( 0.7 3 ) 2 2 ( 0.9 × 0.7 3 } + 2 ( 0.9 × 0.7 3 ) + 0.9 × 0.7 3 { \{ \sqrt [ 3 ]{ 0.9 } ) }^{ 2 }+{ (\sqrt [ 3 ]{ 0.7 } ) }^{ 2 }-2(\sqrt [ 3 ]{ 0.9\times 0.7 } \} +2(\sqrt [ 3 ]{ 0.9\times 0.7 } )+\sqrt [ 3 ]{ 0.9\times 0.7 }

U s i n g a 2 + b 2 2 a b = ( a b ) 2 Using\quad { a }^{ 2 }+{ b }^{ 2 }-2ab={ (a-b) }^{ 2 }

{ ( 0.9 3 0.7 ) 3 ) 2 } + 3 0.63 3 \{ { (\sqrt [ 3 ]{ 0.9 } -\sqrt [ 3 ]{ 0.7) } ) }^{ 2 }\} +3\sqrt [ 3 ]{ 0.63 } \\

B y s u b s t i t u t i n g v a l u e s , ( 0.0775 ) 2 + 0.2 ( 0.0775 ) ( 0.0775 ) 2 By\quad substituting\quad values,\\ { (0.0775) }^{ 2 }+\frac { 0.2 }{ (0.0775) } -{ (0.0775) }^{ 2 }

0.81 3 + 0.49 3 + 0.63 3 = 0.2 0.0775 2 0.81 3 + 0.49 3 + 0.63 3 = 2 0.2 0.0775 = 2 ÷ ( 0.2 0.0775 ) = 2 × ( 0.0775 0.2 ) = 0.775 \Rightarrow \sqrt [ 3 ]{ 0.81 } +\sqrt [ 3 ]{ 0.49 } +\sqrt [ 3 ]{ 0.63 } =\frac { 0.2 }{ 0.0775 } \\\Rightarrow \frac { 2 }{ \sqrt [ 3 ]{ 0.81 } +\sqrt [ 3 ]{ 0.49 } +\sqrt [ 3 ]{ 0.63 } } =\frac { 2 }{ \frac { 0.2 }{ 0.0775 } } =2\div (\frac { 0.2 }{ 0.0775 } )=2\times (\frac { 0.0775 }{ 0.2 } )=0.775

2 0.81 3 + 0.49 3 + 0.63 3 = 0.775 \therefore \frac { 2 }{ \sqrt [ 3 ]{ 0.81 } +\sqrt [ 3 ]{ 0.49 } +\sqrt [ 3 ]{ 0.63 } } =0.775

0 pending reports

×

Problem Loading...

Note Loading...

Set Loading...